"Pee in Peace" or "Make Everyone Uncomfortable": Public Perceptions of Transgender Rights. (November 2021) - Kazyak, Emily; Burke, Kelsy; Kichler, Rosalind; McGraw, Lora
We analyze a survey of Nebraskans as a case study to examine public opinion of transgender rights. Using a mixed-methods design, we find an even divide among mostly cisgender survey respondents on whether transgender people should be able to use the restroom that aligns with their gender identity. Our findings mirror national data and show that identifying as female, being more liberal politically, and being less religious are associated with supporting this belief. Qualitative analysis of open-ended responses reveals that both supporters and opponents of transgender rights employ logics that implicate (1) the nature of transgender identities, (2) the experiences of transgender people, and (3) the regulation of transgender bodies in public spaces. Despite drawing on similar themes, supporters and opponents construct divergent gendered realities that either validate or preclude the recognition of transgender people. Our findings shed light on how the cisgender/transgender binary functions as a facet of inequality.